2021
DOI: 10.3390/su13063393
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Cover and Tumuli’s Shape as Affecting Factors of Microclimate and Biodeterioration Risk for the Conservation of Etruscan Tombs (Tarquinia, Italy)

Abstract: The conservation of underground tombs is affected by several physical-chemical and biological factors, which could be reduced by insulating systems able to maintain the microclimatic stability also decreasing the biodeterioration risk. In Mediterranean areas, wild ephemeral plants, which reduce their cover during the hot season, seem unsuitable for reducing summer overheating. In this study, we wish to assess the influence of vegetation cover and of overlaying soil, after the establishment of an evergreen turf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Vegetation affects the microclimate conditions of the sites and underground structures, decreasing the temperatures and increasing the humidity values. Recent studies in these Etruscan tombs showed some positive potential effects of plant cover in the stabilization of the local microclimate [66]. The negative counterpart is the role played by roots as carriers for rhizosphere microorganisms, water penetration, and organic carbon supply [22,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation affects the microclimate conditions of the sites and underground structures, decreasing the temperatures and increasing the humidity values. Recent studies in these Etruscan tombs showed some positive potential effects of plant cover in the stabilization of the local microclimate [66]. The negative counterpart is the role played by roots as carriers for rhizosphere microorganisms, water penetration, and organic carbon supply [22,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated moisture values and stable temperatures have been reported as ideally suited to promote microbial growth on surfaces in catacombs sites [7,94,141]. Indeed, the highest risk occurs when high humidity is coupled with high temperature values, and negative effects of rising temperatures arise only if their highest values can strongly influence the humidity values [142]. In the case of hypogea, the underground conditions favor the maintaining of humidity.…”
Section: Distribution Of Taxa In the Different Environmentsmentioning
confidence: 99%
“…The diagnostic campaign was also aimed at acquiring comprehensive knowledge of the alteration and degradation forms. The peculiar microclimate conditions, characterized by high relative humidity and constant temperature, represent the optimum for biological species growth [ 16 , 17 ]. The unstable thermohygrometric equilibrium may also be altered by external factors, connected to the heavy flows of visitors, which contribute to increasing the level of risk of biodeterioration phenomena.…”
Section: Discussionmentioning
confidence: 99%